2017
DOI: 10.1038/srep43723
|View full text |Cite
|
Sign up to set email alerts
|

Active directional switching of surface plasmon polaritons using a phase transition material

Abstract: Active switching of near-field directivity, which is an essential functionality for compact integrated photonics and small optoelectronic elements, has been challenging due to small modulation depth and complicated fabrication methods for devices including active optical materials. Here, we theoretically and experimentally realize a nanoscale active directional switching of surface plasmon polaritons (SPPs) using a phase transition material for the first time. The SPP switching device with noticeable distincti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 44 publications
(60 reference statements)
0
16
0
Order By: Relevance
“…Several papers have reported VO 2 -based controllable plasmonic modulators that can be tuned by external stimuli [ 75 , 76 , 78 ]. A grating-based metasurface that exploits the phase transition property of VO 2 has been developed as an active switch of surface plasmon polaritons (SPPs) at the telecom wavelength ( Figure 10 a) [ 79 ]. Illumination by of a monochromatic laser normal to the surface generated two SPPs ( Figure 10 b) [ 79 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Several papers have reported VO 2 -based controllable plasmonic modulators that can be tuned by external stimuli [ 75 , 76 , 78 ]. A grating-based metasurface that exploits the phase transition property of VO 2 has been developed as an active switch of surface plasmon polaritons (SPPs) at the telecom wavelength ( Figure 10 a) [ 79 ]. Illumination by of a monochromatic laser normal to the surface generated two SPPs ( Figure 10 b) [ 79 ].…”
Section: Reviewmentioning
confidence: 99%
“…Theoretical and experimental results confirmed that thermal stimuli can induce active and reversible switching of SPPs. The scattering direction of the nanograting was switched depending on the applied temperature; this phenomenon may cause the phase-transition behavior of VO 2 [ 79 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Achieving unidirectional reflectionless propagation is important for several key applications in photonic circuits such as optical network analyzers [15,19]. In addition, switching of the direction of reflectionless light propagation could be essential for building compact optoelectronic devices, for reducing the size of optical systems, and for developing reconfigurable optical components [31][32][33]. This could be achieved by using materials with tunable optical properties such as phase-change materials.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is commonly referred to as superscattering. Switching between the cloaking and enhanced scattering states could be essential for building compact optoelectronic devices, for reducing the size of optical systems, and for developing reconfigurable optical components [67][68][69][70][71][72][73][74][75][76][77][78][79]. Such switching between the enhanced scattering and invisibility cloaking regimes has been demonstrated using nonlinear materials [70] and quantum emitters [71].…”
Section: Introductionmentioning
confidence: 99%